2001
DOI: 10.1023/a:1013160905497
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The observed weekly rhythm for oocyte pick-ups is certainly due to preprogrammed ovarian stimulation used in our IVF programs. Age as well as the number of embryos transferred are the main influencing factors on a positive outcome and more predictive than seasonal aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 17 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Some studies on season and IVF outcomes have found no association [14][15][16][17][18], while some have suggested higher implantation and livebirth rates for IVF cycles started in the spring and summer [19][20][21]. Other studies have suggested higher positive IVF outcomes for cycles started in the fall and winter [22,23]. To improve understanding of the relationship between seasonal variation and IVF success, we investigated the relationship between season, temperature, and day length at time of oocyte retrieval in a large cohort of more than 6000 IVF cycles performed at one IVF center in Massachusetts over a 6-year period.…”
mentioning
confidence: 99%
“…Some studies on season and IVF outcomes have found no association [14][15][16][17][18], while some have suggested higher implantation and livebirth rates for IVF cycles started in the spring and summer [19][20][21]. Other studies have suggested higher positive IVF outcomes for cycles started in the fall and winter [22,23]. To improve understanding of the relationship between seasonal variation and IVF success, we investigated the relationship between season, temperature, and day length at time of oocyte retrieval in a large cohort of more than 6000 IVF cycles performed at one IVF center in Massachusetts over a 6-year period.…”
mentioning
confidence: 99%
“…In an earlier retrospective analysis of 8184 ART cycles conducted in Europe, Weigert et al . [ 18 ] reported significantly higher pregnancy rates in the colder months September–April (32.2%) versus May–August (28.5%). Investigators concluded that the difference may be attributed to the difference in semen parameters in different seasons.…”
Section: Discussionmentioning
confidence: 99%
“…In a quest for evaluating the effects of seasonal variation on ART, investigators have performed number of studies, however, most of the studies report conflicting results. [ 15 16 17 18 ] While few studies reported poor fertilization and implantation rates in autumn and higher pregnancy rates following ART in spring,[ 15 16 ] others reported significantly higher number of ART conceptions in the winter months. [ 17 18 ] In addition, some investigators further reported no significant difference in fertilization, clinical pregnancy, or LBRs following ART in different seasons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations